Molecular landscape of salivary gland malignancies. What is already known? - Pikul, Julia; Rzepakowska, Anna (Contemporary Oncology/Współczesna Onkologia, 2024)
Salivary gland carcinomas (SGCs) are highly heterogeneous histopathological entities that arise in either the major or minor salivary glands. Although uncommon, these tumours exhibit considerable aggressiveness, unpredictable progression, and significant mortality. The fifth edition of the World Health Organisation classification of head and neck tumours distinguishes between 24 salivary gland malignancies. This may lead to difficulties in terms of diagnostic accuracy and suitable therapeutic selection. Mucoepidermoid carcinoma occurs most frequently and is characterised by gradual disease progression. Although salivary duct carcinoma, myoepithelial carcinoma, and carcinoma ex pleomorphic adenoma are rarely detected, they contribute to poor patient outcomes. Currently, attempts have been made to establish molecular characterisation of SGCs to improve differential diagnosis and create targeted treatments. This study aimed to summarise current knowledge regarding genetic variations in the most common salivary gland malignancies.